Simple mechanical methods for cardioversion: defence of the precordial thump and cough version. Issue 6496 (7th September 1985) - Caldwell, G; Millar, G; Quinn, E; Vincent, R; Chamberlain, D A
Abstract : A prospective study was made of the value of the precordial thump and of cough version in life threatening ventricular arrhythmias. Of about 5000 medical and surgical patients, 68 were treated for persistent ventricular tachycardia and 248 for ventricular fibrillation, 86 of whom had presented outside hospital. Mechanical intervention was successful in 26 incidents occurring in 23 patients. Electrocardiographic records were obtained in 14 instances. Ventricular fibrillation was terminated by a thump in five patients and ventricular tachycardia by either a thump or a cough in a total of 17 patients. Four additional instances were recorded of successful recovery from asystolic or unspecified circulatory arrest after a precordial thump. Fifteen patients survived to be discharged from hospital. The potential benefit of the precordial thump and cough versions greatly outweighs their risks; hence these manoeuvres should probably be reintroduced into schedules for first aid resuscitation.